Desain Inovasi Prototipe Teknologi Solar Distillation untuk Konversi Air Laut menjadi Air Bersih: Indonesia - Wibowo, Dwiprayogo; Pagala, Muh. Imran; Ndibale, Wa; Ilham, Ilham; Sulistyaningrum, Diah Ayu Wulandari (Jurnal Sains & Teknologi Lingkungan, 2026)
Clean water is a fundamental need for coastal and small island communities in Indonesia due to limited freshwater sources and high groundwater salinity caused by seawater intrusion. This study aims to design an innovative prototype of a solar-based seawater distillation technology as a low-cost and environmentally friendly solution. Technology adopts evaporation and condensation principles to convert seawater into clean water that meets quality standards. The distillation device is constructed using simple, corrosion-resistant materials, such as transparent glass, utilizing sunlight as the primary energy source, with condensed water droplets collected through an outlet pipe into a clean-water reservoir. The results demonstrate that the seawater distillation process is highly effective in separating seawater into clean water free from salt content, microorganisms, and impurities. The distillation process can reduce the salt content of seawater by up to 99% ppt and the pH level to 7.5. In addition, the hardness level (66.58 mg/L), nitrate (NO3⁻) (1.10 mg/L), nitrite (NO2⁻) (0.026 mg/L), iron (Fe) (<0.0034 mg/L), and microbiology (MPN Coliform and APM E. Coli = 0 MPN/CFU/100 mL) also decreased in accordance with the standard quality standards for clean water. The cost efficiency and ease of implementation of this technology offer a promising solution for clean water provision, supporting the achievement of sustainable development goals related to clean water and sanitation.